Instructional leadership: Principals’ roles in supporting continuous professional teacher development - Melitta Adams; Yusuf Sayed; Dorothy Esau; Brandon Arendse (Perspectives in Education, 2025)
Principals play an integral role in enhancing the skills and professional development of their teaching staff when they provide constructive feedback to enhance the reflexive capabilities of teachers as determined by teacher education policy (MRTEQ, 2015) and can be the driving force behind their pursuit to provide quality education, as stipulated in Goal 4 of the UNESCO’s Sustainable Development Goals (UNESCO, 2015). This article explores the roles of school principals as instructional leaders in supporting continuous professional teachers’ development (CPTD). The study followed a qualitative research approach, using case studies which involved two schools in the Metropole Central Education District in the Western Cape. Semi-structured interviews were conducted with three teachers from each school. The finding suggests that CPTD plays a significant role in identifying the necessary gaps in pedagogical content knowledge (PCK) and how to manage a class to mitigate disruptive behaviour successfully. The data further highlights how the two principals prioritise CPTD at their schools by being directly or indirectly involved in the CPTD sessions of the staff. The data indicated that teachers want to develop professionally and expect principals to provide them with the freedom to evaluate their performance and identify where they need to grow. To serve the needs of the teachers and continually capacitate teachers, principals and the leadership (SMT) identified appropriate CPTD programmes that will improve teaching and learning, boost intellectual confidence, and eventually enhance learner achievement.